High-strength coating, preparation method and application in SMC (Sheet Molding Compound)
By introducing polyurethane materials and modified zinc oxide whiskers into the coating, a dense three-dimensional network structure is formed, which solves the problems of insufficient wear resistance and yellowing resistance of the coating and achieves a coating effect with high strength and high adhesion.
Patent Information
- Application Number
- CN202511445933.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2025-11-28
- Estimated Expiration
- 2045-10-11
AI Technical Summary
The wear resistance and yellowing resistance of existing coatings need to be improved.
Polyurethane is used as the film-forming material for the coating. By combining aromatic diisocyanate, polyether polyol, polyester polyol and hydroxyl-terminated polydimethylsiloxane, rigid molecular chains and flexible molecular chains are introduced, and modified zinc oxide whiskers are added to form a dense three-dimensional network structure. At the same time, highly reactive epoxy groups and multifunctional groups are introduced and cross-linked by photoinitiator.
It improves the hardness, adhesion and abrasion resistance of the coating, while also improving its resistance to yellowing.
Smart Images

Figure CN121022243A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of coatings, and particularly relates to a high-strength coating, a preparation method and application on SMC. BACKGROUND
[0002] SMC (Sheet molding compound) is generally prepared by impregnating fibers or chopped fiber mats with a resin paste as a resin material and using a polyethylene film as a bearing film, and is molded by molding to have high performance and be capable of replacing steel with plastic and applied to various fields. Coating a coating on the surface to form a protective coating can effectively improve the surface aesthetics, wear resistance, solvent resistance and other properties of SMC.
[0003] Chinese patent CN115011246B discloses a high-strength wear-resistant organic silicon protective coating, and the preparation raw materials include: high molecular weight polydimethylsiloxane, surface modified white carbon black reinforcing filler, pigment, crosslinking agent, tackifier, catalyst, organic solvent, the surface of the white carbon black is modified by hexamethyldisilazane to avoid the agglomeration and structuring of the nano filler, and the modified white carbon black with high specific surface area is matched with a four-functional crosslinking agent and high molecular weight polydimethylsiloxane to improve the high strength, high toughness and high wear resistance of the organic silicon coating. Compared with organic silicon coating, the wear resistance of polyurethane coating is much better than that of organic silicon coating, but the yellowing resistance of polyurethane-based coating needs to be improved. SUMMARY
[0004] In view of the deficiencies of the prior art, the present application provides a high-strength coating, a preparation method and application on SMC to solve the problems that the wear resistance and yellowing resistance of the coating in the prior art need to be improved.
[0005] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is as follows: A preparation method of a high-strength coating, comprising the following steps: Step one, polyether polyol, polyester polyol and hydroxyl-terminated polydimethylsiloxane are added to N,N-dimethylformamide, heated, aromatic diisocyanate and dibutyltin dilaurate are added, and reacted, and after the reaction is completed, a polyurethane prepolymer is obtained; Step two, 1,4-butanediol and an epoxy group-containing diol are added to the polyurethane prepolymer, and reacted, and after the reaction is completed, the temperature is lowered to a set temperature, pentaerythritol triacrylate is added, and the reaction is continued, and after the reaction is completed, a polyurethane mixed solution is obtained; The epoxy group-containing diol is prepared by the following steps: Bisphenol A diglycidyl ether was dissolved in acetone to obtain a bisphenol A diglycidyl ether solution; fumaric acid, hydroquinone and N,N-dimethylethanolamine were dissolved in acetone to obtain a mixed solution containing fumaric acid, hydroquinone and N,N-dimethylethanolamine. The bisphenol A diglycidyl ether solution was stirred and heated to the first set temperature. A mixed solution containing fumaric acid, hydroquinone and N,N-dimethylethanolamine was added dropwise. After the addition was complete, the temperature was raised to the second set temperature and the reaction was allowed to proceed. After the reaction was completed, the solution was cooled, precipitated, purified, and dried to obtain an epoxy-containing diol. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react. After the reaction is complete, add a photoinitiator and stir to obtain a high-strength coating. The modified zinc oxide whiskers are prepared by the following steps: S1. Zinc oxide whiskers are reacted with N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane to obtain amino-modified zinc oxide whiskers; S2, amino-modified zinc oxide whiskers are reacted with 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride to obtain modified zinc oxide whiskers.
[0006] Preferably, in step one, the molar ratio of aromatic diisocyanate, polyether polyol, polyester polyol, and hydroxyl-terminated polydimethylsiloxane is (1.5-2.5):(0.4-0.6):(0.4-0.6):(0.2-0.3), the amount of N,N-dimethylformamide added is 3-5 times the mass of diisocyanate, polyether polyol, bio-based polyester polyol, and hydroxyl-terminated polydimethylsiloxane, the amount of dibutyltin dilaurate added is 0.4%-0.8% of the mass of aromatic diisocyanate, polyether polyol, polyester polyol, and hydroxyl-terminated polydimethylsiloxane, the heating condition is to raise the temperature to 50-60°C under nitrogen protection, and the reaction condition is to react at 70-80°C for 2-4 hours under nitrogen protection.
[0007] Preferably, the aromatic diisocyanate includes 4,4'-diphenylmethane diisocyanate, the polyether polyol includes polypropylene glycol, and the polyester polyol includes polycaprolactone diol.
[0008] Preferably, in step two, the molar ratio of 1,4-butanediol to aromatic diisocyanate is (0.3-0.6):(1.5-2.5), the molar ratio of epoxy-containing diol to aromatic diisocyanate is (0.15-0.25):(1.5-2.5), and the molar ratio of pentaerythritol triacrylate to aromatic diisocyanate is (0.1-0.2):(1.5-2.5). The reaction conditions are: under nitrogen protection, at a temperature of 80-90°C for 2-3 hours, and the reaction is continued under nitrogen protection at a set temperature for 3-4 hours. The set temperature is 65-75℃.
[0009] Preferably, in step two, when preparing the epoxy-containing diol, the molar ratio of bisphenol A diglycidyl ether in the bisphenol A diglycidyl ether solution to that of fumaric acid in the mixed solution containing fumaric acid, hydroquinone, and N,N-dimethylethanolamine is (2.05-2.2):1; the mass ratio of bisphenol A diglycidyl ether to acetone in the bisphenol A diglycidyl ether solution is 1:(10-20); and the amount of acetone used in the mixed solution containing fumaric acid, hydroquinone, and N,N-dimethylethanolamine is equal to the amount of fumaric acid and hydroquinone. The mass ratio of phenol and N,N-dimethylethanolamine is 60-100 times that of the sum of their masses; the mass ratio of hydroquinone is 0.01%-0.03% of the sum of the masses of bisphenol A diglycidyl ether and fumaric acid; and the mass ratio of N,N-dimethylethanolamine is 0.2%-0.6% of the sum of the masses of bisphenol A diglycidyl ether and fumaric acid. The dropping time of the mixed solution containing fumaric acid, hydroquinone, and N,N-dimethylethanolamine is 1-2 hours. The reaction conditions are reflux at a second set temperature until the acid value of the reaction system is ≤5 mg KOH / g. The first set temperature is 70-80℃, and the second set temperature is 90-100℃.
[0010] Preferably, in step three, the mass ratio of polyurethane mixture, modified zinc oxide whiskers, and photoinitiator is 100:(0.5-1):(0.8-1.2), and the reaction conditions are 24-36 h at 80-90℃.
[0011] Preferably, in step three, during the preparation of modified zinc oxide whiskers, step S1 specifically includes: N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was added to a water-acetone solution, the pH was adjusted to 3-5, and after hydrolysis, zinc oxide whiskers were added. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-modified zinc oxide whiskers. The mass ratio of zinc oxide whiskers, water-acetone solution, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane is 8:(100-200):(1-3), and the reaction is carried out under the condition of stirring at 60-80℃ for 1-2 hours.
[0012] Preferably, the water-acetone solution is prepared by mixing deionized water and acetone in a volume ratio of 1:1.
[0013] Preferably, in step three, during the preparation of modified zinc oxide whiskers, step S2 specifically includes: Amino-modified zinc oxide whiskers, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride, and triethylamine were added to N,N-dimethylformamide and reacted. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified zinc oxide whiskers. The mass ratio of amino-modified zinc oxide whiskers, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride, triethylamine, and N,N-dimethylformamide was (8.6-9):(30-32):(1.2-2.6):(200-300), and the reaction was carried out under a nitrogen atmosphere at a temperature of 55-75℃ for 20-30 hours.
[0014] Preferably, in step three, the photoinitiator includes 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0015] The present invention also discloses a high-strength coating prepared by the method described above.
[0016] An application of a high-strength coating as described above on SMC.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: In this invention, polyurethane is used as the film-forming material for the coating, which has high strength, specifically manifested in the high hardness, strong adhesion, and good wear resistance of the cured coating. In the preparation of the polyurethane, aromatic diisocyanate is used. The aromatic ring has a rigid benzene ring structure; introducing it into the polyurethane main chain enhances the rigidity of the polyurethane molecular chain, resulting in a polyurethane material with high wear resistance. The combined use of polyether polyol and polyester polyol also improves the wear resistance, flexibility, and hardness of the polyurethane. The organosilicon molecular chain introduced through hydroxyl-terminated polydimethylsiloxane also improves the flexibility of the polyurethane. With the increase in the flexibility of the polyurethane, it can… This allows the polyurethane and SMC surface polyethylene matrix film to expand and contract synchronously with each other, making them less prone to cracking and exhibiting strong adhesion. The chain extender, an epoxy-containing diol, reacts with diisocyanate to introduce highly reactive epoxy groups into the polyurethane molecular chain. Simultaneously, it can introduce alkenyl groups into the polyurethane molecular chain. Pentaerythritol triacrylate is used to end-cap the polyurethane, introducing multifunctional groups. Under the action of a photoinitiator, the polyurethane can utilize the cross-linking effect between the alkenyl groups introduced into the molecular chain and the multifunctional groups at the end to form a dense three-dimensional network structure. This not only improves the hardness and wear resistance of the polyurethane coating but also enhances the adhesion between the polyurethane coating and the SMC substrate. In this invention, modified zinc oxide whiskers prepared by reacting zinc oxide whiskers with 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride can further improve the strength and wear resistance of polyurethane, while also improving the yellowing resistance of polyurethane. During the preparation of modified zinc oxide whiskers, the imino group introduced by N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane can react with the epoxy groups on the polyurethane molecular chain to achieve chemical bonding between the modified zinc oxide whiskers and the polyurethane molecular chain, resulting in good yellowing resistance. Attached Figure Description
[0018] Figure 1 This is a schematic diagram illustrating the reaction of bisphenol A diglycidyl ether with fumaric acid to prepare an epoxy-containing diol in this invention. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0020] Example 1 This embodiment discloses a method for preparing an epoxy-containing diol, comprising the following steps: Bisphenol A diglycidyl ether was dissolved in acetone at a mass ratio of 1:15 to obtain a bisphenol A diglycidyl ether solution. Fumaric acid, hydroquinone and N,N-dimethylethanolamine were dissolved in acetone, with the amount of acetone being 80 times the sum of the masses of fumaric acid, hydroquinone and N,N-dimethylethanolamine, to obtain a mixed solution. The molar ratio of bisphenol A diglycidyl ether to fumaric acid in the bisphenol A diglycidyl ether solution was 2.1:1. Hydroquinone accounted for 0.02% of the total mass of bisphenol A diglycidyl ether and fumaric acid, and N,N-dimethylethanolamine accounted for 0.4% of the total mass of bisphenol A diglycidyl ether and fumaric acid. The bisphenol A diglycidyl ether solution was stirred at 300 r / min and heated to 80 °C. A mixed solution was added dropwise over 2 h. After the addition was complete, the mixture was stirred at 300 r / min and heated to 100 °C. The mixture was refluxed at 100 °C until the acid value of the reaction system was <5 mg KOH / g. The mixture was then cooled to room temperature. The reaction mixture was added dropwise to an aqueous methanol solution (prepared by mixing methanol and deionized water at a volume ratio of 1:5) with stirring to precipitate the product. The precipitate was dissolved in acetone and then added dropwise to the aqueous methanol solution again to precipitate. This process of dissolution and precipitation was repeated three times. The precipitate was then dried in a vacuum drying oven at 50 °C to constant weight to obtain an epoxy-containing diol.
[0021] Example 2 This embodiment discloses a method for preparing modified zinc oxide whiskers, including the following steps: S1. N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was added to a water-acetone solution (acetone and deionized water were prepared in a volume ratio of 1:1). The pH was adjusted to 4 with 1 mol / L hydrochloric acid. After hydrolysis at room temperature and stirring at 300 r / min for 30 min, zinc oxide whiskers were added. The mass ratio of zinc oxide whiskers, water-acetone solution, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was 8:150:2. The reaction was carried out at 70℃ for 1.5 h with stirring at 300 r / min. After the reaction was completed, the mixture was filtered, washed three times with ethanol, and dried in a vacuum drying oven at 50℃ to constant weight to obtain amino-modified zinc oxide whiskers. S2. Amino-modified zinc oxide whiskers, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride, and triethylamine were added to N,N-dimethylformamide. The mass ratio of amino-modified zinc oxide whiskers, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride, triethylamine, and N,N-dimethylformamide was 8.8:32:2:250. The reaction was carried out under a nitrogen atmosphere at 65°C for 24 hours. After the reaction was completed, the mixture was filtered, washed three times with ethanol, and dried in a vacuum drying oven at 50°C until constant weight was obtained to obtain modified zinc oxide whiskers.
[0022] Example 3 This embodiment discloses a method for preparing a high-strength coating, including the following steps: Step 1: Add polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane to N,N-dimethylformamide. Under nitrogen protection, heat to 50°C, then add 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate. The molar ratio of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane is 1.5:0.4:0.4:0.2. The amount of formamide added was 3 times the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The amount of dibutyltin dilaurate added was 0.4% of the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The reaction was carried out under nitrogen protection at 70°C for 4 hours. After the reaction was completed, a polyurethane prepolymer was obtained. Step 2: Add 1,4-butanediol and the epoxy-containing diol prepared in Example 1 to the polyurethane prepolymer. The molar ratio of 1,4-butanediol to 4,4'-diphenylmethane diisocyanate is 0.3:1.5, and the molar ratio of the epoxy-containing diol to 4,4'-diphenylmethane diisocyanate is 0.15:1.5. React under nitrogen protection at 80°C for 3 hours. After the reaction is completed, cool down to 65°C and add pentaerythritol triacrylate. The molar ratio of pentaerythritol triacrylate to 4,4'-diphenylmethane diisocyanate is 0.1:1.5. React under nitrogen protection at 65°C for 4 hours. After the reaction is completed, a polyurethane mixture is obtained. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react at 80℃ for 36 hours. After the reaction is complete, add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mass ratio of polyurethane mixture, modified zinc oxide whiskers, and 2-hydroxy-2-methyl-1-phenyl-1-propanone is 100:0.5:0.8. Stir at 800 r / min for 30 minutes to obtain a high-strength coating.
[0023] Example 4 This embodiment discloses a method for preparing a high-strength coating, including the following steps: Step 1: Add polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane to N,N-dimethylformamide. Heat to 60°C under nitrogen protection. Add 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate. The molar ratio of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane is 2.5:0.6:0.6:0.3. The amount of formamide added was 5 times the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The amount of dibutyltin dilaurate added was 0.8% of the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The reaction was carried out under nitrogen protection at 80°C for 2 hours. After the reaction was completed, a polyurethane prepolymer was obtained. Step 2: Add 1,4-butanediol and the epoxy-containing diol prepared in Example 1 to the polyurethane prepolymer. The molar ratio of 1,4-butanediol to 4,4'-diphenylmethane diisocyanate is 0.6:1.5, and the molar ratio of the epoxy-containing diol to 4,4'-diphenylmethane diisocyanate is 0.25:1.5. React under nitrogen protection at 90°C for 2 hours. After the reaction is completed, cool down to 75°C and add pentaerythritol triacrylate. The molar ratio of pentaerythritol triacrylate to 4,4'-diphenylmethane diisocyanate is 0.2:1.5. React under nitrogen protection at 75°C for 3 hours. After the reaction is completed, a polyurethane mixture is obtained. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react at 90℃ for 24 hours. After the reaction is complete, add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mass ratio of polyurethane mixture, modified zinc oxide whiskers, and 2-hydroxy-2-methyl-1-phenyl-1-propanone is 100:1:1.2. Stir at 800 r / min for 30 minutes to obtain a high-strength coating.
[0024] Example 5 This embodiment discloses a method for preparing a high-strength coating, including the following steps: Step 1: Add polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane to N,N-dimethylformamide. Under nitrogen protection, heat to 55°C, then add 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate. The molar ratio of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane is 1.8:0.45:0.45:0.22. The amount of methylformamide added was 4 times the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The amount of dibutyltin dilaurate added was 0.5% of the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The reaction was carried out under nitrogen protection at 75°C for 3 hours. After the reaction was completed, a polyurethane prepolymer was obtained. Step 2: Add 1,4-butanediol and the epoxy-containing diol prepared in Example 1 to the polyurethane prepolymer. The molar ratio of 1,4-butanediol to 4,4'-diphenylmethane diisocyanate is 0.4:1.8, and the molar ratio of the epoxy-containing diol to 4,4'-diphenylmethane diisocyanate is 0.18:1.8. React under nitrogen protection at 85°C for 2.5 h. After the reaction is completed, cool down to 70°C and add pentaerythritol triacrylate. The molar ratio of pentaerythritol triacrylate to 4,4'-diphenylmethane diisocyanate is 0.12:1.8. React under nitrogen protection at 70°C for 3.5 h. After the reaction is completed, a polyurethane mixture is obtained. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react at 85℃ for 30 hours. After the reaction is complete, add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mass ratio of polyurethane mixture, modified zinc oxide whiskers, and 2-hydroxy-2-methyl-1-phenyl-1-propanone is 100:0.6:0.9. Stir at 800 r / min for 30 minutes to obtain a high-strength coating.
[0025] Example 6 This embodiment discloses a method for preparing a high-strength coating, including the following steps: Step 1: Add polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane to N,N-dimethylformamide. Under nitrogen protection, heat to 55°C, then add 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate. The molar ratio of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane is 2:0.5:0.5:0.25. The amount of formamide added was 4 times the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The amount of dibutyltin dilaurate added was 0.6% of the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The reaction was carried out under nitrogen protection at 75°C for 3 hours. After the reaction was completed, a polyurethane prepolymer was obtained. Step 2: Add 1,4-butanediol and the epoxy-containing diol prepared in Example 1 to the polyurethane prepolymer. The molar ratio of 1,4-butanediol to 4,4'-diphenylmethane diisocyanate is 0.45:2, and the molar ratio of the epoxy-containing diol to 4,4'-diphenylmethane diisocyanate is 0.2:2. React under nitrogen protection at 85°C for 2.5 h. After the reaction is completed, cool down to 70°C and add pentaerythritol triacrylate. The molar ratio of pentaerythritol triacrylate to 4,4'-diphenylmethane diisocyanate is 0.15:2. React under nitrogen protection at 70°C for 3.5 h. After the reaction is completed, a polyurethane mixture is obtained. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react at 85℃ for 30 hours. After the reaction is complete, add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mass ratio of polyurethane mixture, modified zinc oxide whiskers, and 2-hydroxy-2-methyl-1-phenyl-1-propanone is 100:0.75:1. Stir at 800 r / min for 30 minutes to obtain a high-strength coating.
[0026] Example 7 This embodiment discloses a method for preparing a high-strength coating, including the following steps: Step 1: Add polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane to N,N-dimethylformamide. Under nitrogen protection, heat to 55°C, then add 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate. The molar ratio of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane is 2.3:0.55:0.55:0.27. The amount of methylformamide added was 4 times the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The amount of dibutyltin dilaurate added was 0.7% of the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The reaction was carried out under nitrogen protection at 75°C for 3 hours. After the reaction was completed, a polyurethane prepolymer was obtained. Step 2: Add 1,4-butanediol and the epoxy-containing diol prepared in Example 1 to the polyurethane prepolymer. The molar ratio of 1,4-butanediol to 4,4'-diphenylmethane diisocyanate is 0.5:2.3, and the molar ratio of the epoxy-containing diol to 4,4'-diphenylmethane diisocyanate is 0.22:2.3. React under nitrogen protection at 85°C for 2.5 h. After the reaction is completed, cool down to 70°C and add pentaerythritol triacrylate. The molar ratio of pentaerythritol triacrylate to 4,4'-diphenylmethane diisocyanate is 0.18:2.3. React under nitrogen protection at 70°C for 3.5 h. After the reaction is completed, a polyurethane mixture is obtained. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react at 85℃ for 30 hours. After the reaction is complete, add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mass ratio of polyurethane mixture, modified zinc oxide whiskers, and 2-hydroxy-2-methyl-1-phenyl-1-propanone is 100:0.9:1.1. Stir at 800 r / min for 30 minutes to obtain a high-strength coating.
[0027] Comparative Example 1 This comparative example discloses a method for preparing a high-strength coating, comprising the following steps: Step 1: Add polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane to N,N-dimethylformamide. Under nitrogen protection, heat to 50°C, then add 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate. The molar ratio of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane is 1.5:0.4:0.4:0.2. The amount of formamide added was 3 times the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The amount of dibutyltin dilaurate added was 0.4% of the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The reaction was carried out under nitrogen protection at 70°C for 4 hours. After the reaction was completed, a polyurethane prepolymer was obtained. Step 2: Add 1,4-butanediol to the polyurethane prepolymer. The molar ratio of 1,4-butanediol to 4,4'-diphenylmethane diisocyanate is 0.45:1.5. React at 80°C for 3 hours under nitrogen protection. After the reaction is complete, cool down to 65°C and add pentaerythritol triacrylate. The molar ratio of pentaerythritol triacrylate to 4,4'-diphenylmethane diisocyanate is 0.1:1.5. React at 65°C for 4 hours under nitrogen protection. After the reaction is complete, a polyurethane mixture is obtained. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react at 80℃ for 36 hours. After the reaction is complete, add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mass ratio of polyurethane mixture, modified zinc oxide whiskers, and 2-hydroxy-2-methyl-1-phenyl-1-propanone is 100:0.5:0.8. Stir at 800 r / min for 30 minutes to obtain a high-strength coating.
[0028] Comparative Example 2 This comparative example discloses a method for preparing a high-strength coating, comprising the following steps: Step 1: Add polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane to N,N-dimethylformamide. Under nitrogen protection, heat to 50°C, then add 4,4'-diphenylmethane diisocyanate and dibutyltin dilaurate. The molar ratio of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane is 1.5:0.4:0.4:0.2. The amount of formamide added was 3 times the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The amount of dibutyltin dilaurate added was 0.4% of the mass of 4,4'-diphenylmethane diisocyanate, polypropylene glycol, polycaprolactone glycol, and hydroxyl-terminated polydimethylsiloxane. The reaction was carried out under nitrogen protection at 70°C for 4 hours. After the reaction was completed, a polyurethane prepolymer was obtained. Step 2: Add 1,4-butanediol and the epoxy-containing diol prepared in Example 1 to the polyurethane prepolymer. The molar ratio of 1,4-butanediol to 4,4'-diphenylmethane diisocyanate is 0.3:1.5, and the molar ratio of the epoxy-containing diol to 4,4'-diphenylmethane diisocyanate is 0.15:1.5. React under nitrogen protection at 80°C for 3 hours. After the reaction is completed, cool down to 65°C and add pentaerythritol triacrylate. The molar ratio of pentaerythritol triacrylate to 4,4'-diphenylmethane diisocyanate is 0.1:1.5. React under nitrogen protection at 65°C for 4 hours. After the reaction is completed, a polyurethane mixture is obtained. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react at 80℃ for 36 hours. After the reaction is complete, add the photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone. The mass ratio of polyurethane mixture, modified zinc oxide whiskers, and 2-hydroxy-2-methyl-1-phenyl-1-propanone is 100:0.5:0.8. Stir at 800 r / min for 30 minutes to obtain a high-strength coating. The modified zinc oxide whiskers are prepared by the following steps: S1. Add γ-aminopropyltriethoxysilane to a water-acetone solution (acetone and deionized water are prepared in a volume ratio of 1:1), adjust the pH to 4 with 1 mol / L hydrochloric acid, and hydrolyze at room temperature with stirring at 300 r / min for 30 min. Then add zinc oxide whiskers. The mass ratio of zinc oxide whiskers, water-acetone solution and γ-aminopropyltriethoxysilane is 8:150:2. React at 70℃ with stirring at 300 r / min for 1.5 h. After the reaction is completed, filter, wash three times with ethanol, and dry in a vacuum drying oven at 50℃ to constant weight to obtain amino-modified zinc oxide whiskers. S2. Amino-modified zinc oxide whiskers, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride, and triethylamine were added to N,N-dimethylformamide. The mass ratio of amino-modified zinc oxide whiskers, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride, triethylamine, and N,N-dimethylformamide was 8.8:32:2:250. The reaction was carried out under a nitrogen atmosphere at 65°C for 24 hours. After the reaction was completed, the mixture was filtered, washed three times with ethanol, and dried in a vacuum drying oven at 50°C until constant weight was obtained to obtain modified zinc oxide whiskers.
[0029] In the above examples and comparative examples, the zinc oxide whiskers are tetraneedle-shaped zinc oxide whiskers with a diameter of 0.5-5 μm and a length of 10-50 μm; the polypropylene glycol is PPG-600 with a molecular weight of 600; the polycaprolactone glycol is PCL1000 with a molecular weight of 1000; and the hydroxyl-terminated polydimethylsiloxane has a molecular weight of 1000.
[0030] Test case A transparent polyethylene film with a thickness of 0.05 mm was selected as the substrate. The coatings prepared in Examples 3-7 and Comparative Examples 1-2 were sprayed onto the polyethylene film, with a wet film thickness of 25 ± 5 μm. The irradiation energy was 500 mJ / cm². 2 The coating was cured under ultraviolet light and then placed at room temperature for 24 hours before performance testing was performed. (1) Hardness test: The surface hardness of the coating was tested according to the standard GB / T6739-2006 "Determination of Hardness of Paints and Varnishes by Pencil Method". The test results are shown in Table 1. Table 1 As shown in Table 1, the coating prepared by this invention has high strength and high surface hardness after curing. During the preparation of polyurethane, alkenyl groups and terminal multifunctional groups are introduced into the polyurethane molecular chain. Under the action of a photoinitiator, these groups can crosslink to form a dense three-dimensional network structure, giving the coating high hardness. Simultaneously, the introduction of rigid structures and inorganic filler zinc oxide whiskers also improves the hardness of the polyurethane. Compared with Example 3, in Comparative Example 1, the epoxy-containing diol portion of the chain extender was replaced by 1,4-butanediol. The lack of alkenyl groups in the epoxy-containing diol weakened the crosslinking effect between the polyurethane molecular chains, resulting in a significant decrease in the surface hardness of the coating.
[0031] (2) Adhesion test: The adhesion of the coating was tested according to the standard GB / T5210-2006 "Paints and Varnishes - Pull-off Adhesion Test". The test results are shown in Table 2. Table 2 As shown in Table 2, the coating prepared by this invention exhibits strong adhesion to polyethylene after curing. The introduction of flexible molecular chains improves the flexibility of polyurethane, enabling the polyurethane and polyethylene matrix film to expand and contract synchronously with each other, reducing cracking and enhancing adhesion. Furthermore, the epoxy-containing diol chain extender introduces alkenyl groups into the polyurethane molecular chain, and pentaerythritol triacrylate acts as a capping agent, introducing multifunctional groups. The polyurethane utilizes the cross-linking effect between the introduced alkenyl groups and the terminal multifunctional groups in the molecular chain to form a dense three-dimensional network structure, thereby improving the adhesion between the polyurethane coating and polyethylene. Compared to Example 3, in Comparative Example 1, the epoxy-containing diol chain extender was replaced by 1,4-butanediol, lacking the introduction of alkenyl groups from the epoxy-containing diol. This weakened the cross-linking effect between the polyurethane molecular chains, resulting in decreased adhesion to the polyethylene film.
[0032] (3) Abrasion resistance test: The RCA abrasion resistance of the coating was tested according to ASTM F2357. The test results are shown in Table 3. Table 3 As shown in Table 3, the coating prepared by this invention exhibits good wear resistance after curing. In the preparation of polyurethane, the use of aromatic diisocyanate enhances the rigidity of the polyurethane molecular chain, resulting in high wear resistance. The combined use of polyether polyol and polyester polyol also improves the wear resistance of polyurethane. The alkenyl groups introduced into the polyurethane molecular chain and the multifunctional groups introduced at the polyurethane end positions crosslink under the action of a photoinitiator to form a dense three-dimensional network structure, which also improves the wear resistance of polyurethane. Finally, the introduction of zinc oxide whiskers further enhances the wear resistance of polyurethane. Compared with Example 3, in Comparative Example 1, the epoxy-containing diol portion of the chain extender was replaced by 1,4-butanediol. The introduction of alkenyl groups in the epoxy-containing diol was lacking, which weakened the cross-linking effect between polyurethane molecular chains and reduced the wear resistance of polyurethane. In Comparative Example 2, when preparing modified zinc oxide whiskers, the silane coupling agent was replaced by γ-aminopropyltriethoxysilane instead of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane. The chemical bonding between imino groups and epoxy groups on the polyurethane molecular chains was lacking, and the wear resistance was also reduced.
[0033] (4) Yellowing resistance test: The coated polyethylene film was subjected to thermo-oxidative treatment at 140℃ for 500h and ultraviolet irradiation treatment at UVA 340nm for 500h. The color change value of the coating before and after treatment, i.e. color difference (ΔE), was measured. The test results are shown in Table 4: Table 4 As shown in Table 4, the coating prepared by this invention exhibits good resistance to yellowing. The hindered phenolic structure in the zinc oxide whisker and 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride molecule can respectively improve the UV resistance and heat-oxidative yellowing resistance of polyurethane. Furthermore, the imino groups introduced during the reaction of zinc oxide whiskers with 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride to prepare modified zinc oxide whiskers can react with the epoxy groups on the polyurethane molecular chain, achieving chemical bonding between the modified zinc oxide whiskers and the polyurethane molecular chain, resulting in good resistance to yellowing. Compared with Example 3, in Comparative Example 2, when preparing modified zinc oxide whiskers, the silane coupling agent was replaced by γ-aminopropyltriethoxysilane instead of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, lacking the chemical bonding between the imino groups and the epoxy groups on the polyurethane molecular chain, the resistance to yellowing decreased.
[0034] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-strength coating, characterized in that, Includes the following steps: Step 1: Add polyether polyol, polyester polyol, and hydroxyl-terminated polydimethylsiloxane to N,N-dimethylformamide, heat, add aromatic diisocyanate and dibutyltin dilaurate, and react. After the reaction is complete, a polyurethane prepolymer is obtained. Step 2: Add 1,4-butanediol and an epoxy-containing diol to the polyurethane prepolymer and react. After the reaction is complete, cool down to the set temperature, add pentaerythritol triacrylate, and continue the reaction. After the reaction is complete, a polyurethane mixture is obtained. The epoxy-containing diol is prepared by the following steps: The bisphenol A diglycidyl ether solution was stirred and heated to the first set temperature. A mixed solution containing fumaric acid, hydroquinone and N,N-dimethylethanolamine was added dropwise. After the addition was complete, the temperature was raised to the second set temperature and the reaction was allowed to proceed. After the reaction was completed, the solution was cooled, precipitated, purified, and dried to obtain an epoxy-containing diol. Step 3: Add modified zinc oxide whiskers to the polyurethane mixture and react. After the reaction is complete, add a photoinitiator and stir to obtain a high-strength coating. The modified zinc oxide whiskers are prepared by the following steps: S1. Zinc oxide whiskers are reacted with N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane to obtain amino-modified zinc oxide whiskers; S2, amino-modified zinc oxide whiskers are reacted with 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride to obtain modified zinc oxide whiskers.
2. The method for preparing a high-strength coating according to claim 1, characterized in that, In step one, the molar ratio of aromatic diisocyanate, polyether polyol, polyester polyol, and hydroxyl-terminated polydimethylsiloxane is (1.5-2.5):(0.4-0.6):(0.4-0.6):(0.2-0.3). The heating condition is to raise the temperature to 50-60℃ under nitrogen protection, and the reaction condition is to react at 70-80℃ for 2-4 hours under nitrogen protection.
3. The method for preparing a high-strength coating according to claim 2, characterized in that, The aromatic diisocyanate includes 4,4'-diphenylmethane diisocyanate, the polyether polyol includes polyoxypropylene glycol, and the polyester polyol includes polycaprolactone diol.
4. The method for preparing a high-strength coating according to claim 1, characterized in that, In step two, the molar ratio of 1,4-butanediol to aromatic diisocyanate is (0.3-0.6):(1.5-2.5), the molar ratio of epoxy-containing diol to aromatic diisocyanate is (0.15-0.25):(1.5-2.5), and the molar ratio of pentaerythritol triacrylate to aromatic diisocyanate is (0.1-0.2):(1.5-2.5). The reaction conditions are: under nitrogen protection, at a temperature of 80-90℃ for 2-3 hours, and the reaction is continued under nitrogen protection at a set temperature for 3-4 hours. The set temperature is 65-75℃.
5. The method for preparing a high-strength coating according to claim 1, characterized in that, In step two, when preparing the epoxy-containing diol, the molar ratio of bisphenol A diglycidyl ether in the bisphenol A diglycidyl ether solution to that of fumaric acid in the mixed solution containing fumaric acid, hydroquinone and N,N-dimethylethanolamine is (2.05-2.2):
1. The reaction conditions are that the reaction is refluxed at a second set temperature until the acid value of the reaction system is ≤5 mgKOH / g. The first set temperature is 70-80℃, and the second set temperature is 90-100℃.
6. The method for preparing a high-strength coating according to claim 1, characterized in that, In step three, the mass ratio of polyurethane mixture, modified zinc oxide whiskers, and photoinitiator is 100:(0.5-1):(0.8-1.2), and the reaction conditions are 24-36 h at 80-90℃.
7. The method for preparing a high-strength coating according to claim 1, characterized in that, In step three, during the preparation of modified zinc oxide whiskers, step S1 specifically includes: N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane was added to a water-acetone solution, the pH was adjusted to 3-5, and after hydrolysis, zinc oxide whiskers were added. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino-modified zinc oxide whiskers. The mass ratio of zinc oxide whiskers, water-acetone solution, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane is 8:(100-200):(1-3), and the reaction is carried out under the condition of stirring at 60-80℃ for 1-2 hours.
8. The method for preparing a high-strength coating according to claim 1, characterized in that, In step three, during the preparation of modified zinc oxide whiskers, step S2 specifically includes: Amino-modified zinc oxide whiskers, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride, and triethylamine were added to N,N-dimethylformamide and reacted. After the reaction was completed, the mixture was filtered, washed, and dried to obtain modified zinc oxide whiskers. The mass ratio of amino-modified zinc oxide whiskers, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl chloride, triethylamine, and N,N-dimethylformamide was (8.6-9):(30-32):(1.2-2.6):(200-300), and the reaction was carried out under a nitrogen atmosphere at a temperature of 55-75℃ for 20-30 hours.
9. A high-strength coating prepared by the method for preparing high-strength coatings as described in any one of claims 1-8.
10. The application of the high-strength coating as described in claim 9 on SMC.
Citation Information
Patent Citations
High-strength wear-resistant silicone protective coating and its preparation method
CN115011246B
Coating composition
CA2004540A1
Multiple crosslinking ultraviolet light solidifying water polyurethane dispersoid and its preparation method and application
CN101235148A
Polyurethane coating for shoes and manufacturing method of coating of polyurethane coating
CN114479628A
One-step molded polyurethane synthetic leather and polyurethane surface layer resin for same
CN116103937A